Adult-Onset Leukoencephalopathy with Axonal Spheroid and Pigmented Glia: Different Histological Spectrums Presented in Autopsy Cases of Siblings and a Surgical Case of Stereotactic Biopsy - Hee Jung Kwon; Duk L. Na; Hee Jin Kim; Yeon-Lim Suh (Diagnostics, 2023)
Adult-onset leukoencephalopathy with axonal spheroids and pigmented glia encompasses hereditary diffuse leukoencephalopathy with axonal spheroids and pigmented orthochromatic leukodystrophy. We describe the clinicopathological and genetic findings of three patients with this disorder. All patients presented with dysarthria, with or without cognitive decline. The first and second patients were siblings who died of the disease at ages 42 and 54, respectively, while the third patient has been bedridden. Brain magnetic resonance imaging revealed T2 hyperintensities in the subcortical and periventricular white matter. Pathological diagnosis was established by brain autopsy in cases 1 and 2, and a stereotactic brain biopsy in case 3, followed by genetic analysis of colony stimulating factor-1 receptor gene. A heterozygous c.2345G > A (p.R782H) variant was identified in the autopsy-proven cases, and a c.1765G > A (p.G589R) variant in the biopsy-proven case. Postmortem examination revealed severe white matter degeneration involving the bilateral frontoparietal lobes, but sparing the subcortical U-fibers. All cases revealed widespread loss of myelinated axons in the white matter lesions; however, axonal spheroids and pigmented macrophages were abundant in cases 1 and 3 and much less in case 2. Adult-onset leukoencephalopathy with axonal spheroids and pigmented glia should be considered in patients with presenile dementia and diffuse white matter lesions.